Efeitos da evolução do salário mínimo no Brasil sobre a distribuição de renda entre categorias de trabalhadores: uma análise não-paramétrica - Sampaio Filho, Paulo Abreo (2006)
This study analyzes the effect of the minimum wage trend in Brazil on labor income the distribution, as well as the flow of workers, between bands of labor income demarcated by one and two minimum wages, in consequence of the increase in minimum wage verified in the period 1995 the 2003. Workers were grouped in different categories, in order to improve detailing in the analysis. The PNADs (National Research of Sample for Domicile) data for the 1995 - 2003 series were used, applying a not-parametric methodology, with the use of estimator Kernel, to estimate the densities of workers’ income. The results are visual and qualitative and show that some categories had significant changes in the ratio of workers with lesser or equal than a minimum wage and others experienced a strong flow of workers with bigger than two minimum wages in direction to incomes between one and two minimum wages and lesser incomes that a minimum wage.